Irony and joking in ethnographic fieldwork: Reflections from Santo Antão Island (Cape Verde) - Martina Giuffrè (Anuac, 2016)
In this essay I address the crucial role of irony and joking in anthropology with a focus on the ethnographic relationship. My starting point is field research carried out from 2001 to 2004 on Santo Antão island (Cape Verde), specifically Ponta do Sol. In Cape Verdean practice, jokes and irony represent customary communicational modes and important tools for building relationships: the ultimate means of achieving “cultural intimacy”, they are used almost as rites of initiation to bring newcomers into the community and at the same time to manage ambiguities. Indeed, it was precisely through irony that my interlocutors were able to perfectly capture my ambiguous insider/outsider position. In this specific ethnographic context, the ironic relationship is understood as both a key communication tool in the ethnographic encounter and an unusual rite of passage: although strangers/anthropologists can only be accepted if they become Cape Verdean to some degree, in reality they are never really able to complete this passage. The essay briefly reviews irony and joking in anthropology and focuses on aspects of ironic interactions in Cape Verde that are linked to intercultural relations in the ethnographic context as a site of uncertain communication. I stress how, especially in intercultural contexts, the ambiguity of irony represents not a barrier to communication but rather a key element of understanding between anthropologists and informants as well as a significant heuristic device.